CITRA WANITA TOKOH CINTA DALAM NOVEL CINTA DI UJUNG SAJADAH KARYA ASMA NADIA (KAJIAN ANALISIS ISI) - Tika Utama; Sumiharti Sumiharti (Universitas Batanghari, 2021)
This research aims to describe the image of women as children in the novel Cinta di Ujung Sajadah by Asma Nadia, which refers to three aspects, namely: the aspect of tenderness, compassion, and patience. This research includes a qualitative descriptive study. Qualitative descriptive understanding is a type of research used to understand phenomena experienced by research subjects by describing them in the form of words and languages using data from research results in a novel. The data in the novel is in the form of excerpts from the aspects of tenderness, compassion, and patience in the character of Cinta in the novel Cinta di Ujung Sajadah by Asma Nadia. Based on the results of the research, it can be concluded that the image of women as children contained in the novel Cinta di Ujung Sajadah by Asma Nadia consists of three aspects, namely: aspects of tenderness, compassion, and patience, which occurred as many as fifty-six quotations contained in the novel Cinta di Ujung Sajadah. The most dominant aspect is the aspect of patience, being patient of complaints and anger in carrying out God's command, which is found from twenty-two expressions. The second dominant aspect is the aspect of tenderness found from 20 expressions, in which tenderness is a feeling that a person has to speak the word meekly towards others. Furthermore, a little dominant aspect that is compassionate found as many as fourteen expressions in the daily life of compassion which can be interpreted as attitudes and behaviours that reflect the element of giving attention. Thus in this research, there are fifteen expressions of compassionate aspect found.